2018
DOI: 10.3390/en11092446
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Renewable Energy Incentives and Parameter Uncertainties on Financial Feasibility of a Campus Microgrid

Abstract: The popularity of microgrids is increasing considerably because of their environmental and technical advantages. However, the major challenge in microgrid integration is its financial feasibility due to high capital costs. To address this obstacle, renewable energy incentive programs, which are the motivation of this study, have been proposed in many countries. This paper provides a comprehensive evaluation of the technical and financial feasibility of a campus microgrid based on a techno-economic analysis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Their findings showed that renewable energy incentives, tax reductions, and grid services have a significant impact on the financial feasibility of such systems and on the main economic and technical indicators of the microgrid. In a later study, the authors of [34] used the MDSTool to evaluate the effects of different policy measures on the optimal deployment of a microgrid in California. The objective function of the model maximized the profit of the project over the 25-year expected lifetime of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings showed that renewable energy incentives, tax reductions, and grid services have a significant impact on the financial feasibility of such systems and on the main economic and technical indicators of the microgrid. In a later study, the authors of [34] used the MDSTool to evaluate the effects of different policy measures on the optimal deployment of a microgrid in California. The objective function of the model maximized the profit of the project over the 25-year expected lifetime of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The direct reciprocity of peer-to-peer (P2P) energy trading by the association of prosumers contributes to a dramatic decrease in transmission losses and the minimization of the operational costs in smart residential communities. However, most studies regarding the productive management of Microgrids have been dedicated merely to economic incentives for financial sustainability and energy interchanges with the Smart Grids [17,18].…”
Section: Motivation Of Prosumer Scheduling For Microgridsmentioning
confidence: 99%
“…Many studies can be found in literature analyzing microgrids' financial feasibility and the correct sizing of their respective Distributed Energy Resources (DERs) [3,4]. In most of the published works the main objective of the microgrid energy management system is to achieve the highest possible economic benefit by minimizing its operational costs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Generation costs [6] and market prices, for the purchased/sold energy [5], are used to define optimization techniques' objective functions. However, economic incentives and additional costs have a great importance in the microgrids' financial sustainability and they must be considered in their design and operation [3]. Incentives are due to advantages of self-consumption improvement, that lie on empowering consumers by means of their participation in energy management programs, encouraging smarter consumption patterns, reducing peak demand and energy costs, decreasing transmission losses, due to the local generation and consumption, and contributing to finance energy transition [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation